The influence of environment, predisposing, enabling and need variables on personal health choices of adults with intellectual disability. - MC CARRON, MARY (My University, 2013)
Attention to disease and risk factor management is increasingly a feature of people with intellectual disability (ID) as an augmented life expectancy also exposes a growing number of age-related diseases. An additional concern is little attention to date to physical activity, nutrition, access to social support and other personal health choices and to environmental issues such as the impact of access to social support and the implications of individual’s living arrangements. Method: Using a sample of 753 persons with ID from the intellectual disability supplement to the Irish longitudinal study on ageing (IDS-TILDA), forty three variables were grouped into environmental, predisposing, enabling, need and personal health choices clusters and hierarchical ordinary least squares regression examined the contribution of environmental, enabling, predisposing, need and all combinations of the sets of variables to personal health choices. Findings: Almost 32% of variance was explained primarily by need variables. Most significant relationships were with meeting up with family and friends (environmental), age, rating of health and worries about getting older (predisposing), having public health insurance and nursing who come into the home (enabling) and presence of stroke, chronic constipation, functional limitations, high assistance needs with activities of daily living (need). Discussion: Taken together, the groupings of variables from the Anderson Model explained a modest amount of variance in the pursuit of positive personal health choices by people with ID. More work is clearly needed in developing evidence-based interventions and strategies, and in understanding the relationship between positive personal health choices of people with ID and health outcomes.
PUBLISHED
Keywords: Chronic Conditions; Intellectual Disability; Personal Health Choices